Colombia : Development and Peace in the Magdalena Medio Region - World Bank (Washington, DC, 2012)
Magdalena Medio is one of the poorest and most violent areas of Colombia and a microcosm of the actors and issues underlying Colombia's armed conflict with guerrillas, right-wing paramilitaries, with the army battling for control while the civilian population struggles to survive. The region contains great natural and productive wealth with unequal access. The Program for Development and Peace in Magdalena Medio (PDPMM) seeks solutions to the persistent poverty and increasing violence. Its guiding principles were the need to involve and reflect the concerns of all the region's citizens, and the belief that poverty and violence are complex, interrelated problems which must be tackled simultaneously. The Program, which began in 1995 with a diagnostic phase, embodies a long-term vision for community-led, comprehensive development of the region. It aims to increase living standards and reduce violence by creating the conditions necessary for relationships to develop among communities, NGOs, the business sector, various levels of government and, as appropriate, the armed actors. The project was one of the first Bank lending operations in a new area: peace and development. The project demonstrated that, for a participatory approach to succeed in such a complex and challenging environment, there is no substitute for a design which explicitly incorporates flexibility, close monitoring and analysis of the socio-political situation and a mechanism for feeding this back into the program.